Harvesting Agile Wallabies for human consumption in the Northern Territory of Australia. (2nd November 2021) - Hunt, Warren; Bedoya‐Perez, Miguel; Geesink, Geert; Van Den Heuvel, Aaron; Mullen, John; Frost, David
Summary: Agile Wallaby (Notamacropus agilis) has been in the diet of Aboriginal inhabitants of northern Australia for millennia. The species inhabits riparian zones and savannah woodlands, has a high rate of natural increase and can become pests in modified agricultural or plantation systems. Although the profitability of market‐based game harvesting appears marginal, local consumption could be incorporated into existing employment programmes on Aboriginal lands as a social enterprise. The legal environment is discussed, and further investigation and a trial as a pilot enterprise are recommended.